Variation in mutation, recombination, and transposition rates in Drosophila melanogaster and Drosophila simulans - Wang, Yiguan; McNeil, Paul; Abdulazeez, Rashidatu; Pascual, Marta; Johnston, Susan E.; Keightley, Peter D.; Obbard, Darren J. (Genome Research, 2023)
The rates of mutation, recombination, and transposition are core parameters in models of evolution. They impact genetic diversity, responses to ongoing selection, and levels of genetic load. However, even for key evolutionary model species such as Drosophila melanogaster and Drosophila simulans, few estimates of these parameters are available, and we have little idea of how rates vary between individuals, sexes, or populations. Knowledge of this variation is fundamental for parameterizing models of genome evolution. Here, we provide direct estimates of mutation, recombination, and transposition rates and their variation in a West African and a European population of D. melanogaster and a European population of D. simulans. Across 89 flies, we observe 58 single-nucleotide mutations, 286 crossovers, and 89 transposable element (TE) insertions. Compared to the European D. melanogaster, we find the West African population has a lower mutation rate (1.67 × 10−9 site−1 gen−1 vs. 4.86 × 10−9 site−1 gen−1) and a lower transposition rate (8.99 × 10−5 copy−1 gen−1 vs. 23.36 × 10−5 copy−1 gen−1), but a higher recombination rate (3.44 cM/Mb vs. 2.06 cM/Mb). The European D. simulans population has a similar mutation rate to European D. melanogaster, but a significantly higher recombination rate and a lower, but not significantly different, transposition rate. Overall, we find paternal-derived mutations are more frequent than maternal ones in both species. Our study quantifies the variation in rates of mutation, recombination, and transposition among different populations and sexes, and our direct estimates of these parameters in D. melanogaster and D. simulans will benefit future studies in population and evolutionary genetics.
10.1101/gr.277383.122